A Validity and Reliability of the SOLO-Based Assessment in Language Proficiency of Incoming Seventh-Grade Students - Caracol, Jeriel; Altaya, Gracelyn (International Journal of Arts, Sciences and Education, 2025)
This study evaluates the validity and reliability of the SOLO-Based assessment in measuring the language proficiency of incoming seventh-grade students. Using a research and development design, a 50-item test aligned with DepEd Order No. 8, s. 2015, was developed and administered to 68 students from three schools in Norala, South Cotabato. The assessment focused on semantics and grammar, revealing that while students demonstrated satisfactory proficiency in connotation and denotation, their grammatical skills needed improvement. Expert evaluation confirmed the test’s strong alignment with its objectives, validating its effectiveness as an assessment tool. Reliability analysis indicated that the test was consistent and applicable for broader use. ANOVA results showed no significant differences in language proficiency among students from different schools. Overall, the findings affirm that the SOLO-Based assessment is a valid and reliable instrument for evaluating students' language proficiency, with recommendations to enhance grammatical competence further. This will enhances language education by identifying effective teaching strategies and assessment methods, providing valuable insights for improving instruction and addressing linguistic challenges.